Analysis of insurance companie's efficiency in the Republic of Serbia - Radojko Lukic; Miro Sokic; Dragana Vojteski Kljenak (Economic and Environmental Studies (E&ES), 2018)
Lately, as it is known, considerable theoretical and practical attention has been dedicated to the problems of analysing the business efficiency of insurance companies, both worldwide and in particular countries. In view of this, the paper conveys a complex analysis of the 2016 business efficiency of insurance companies in the Republic of Serbia, using theoretical, methodological and empirical knowledge. Over 60% of Serbian insurance market is controlled by only three insurance companies. Out of the 16 insurance companies, 11 are inefficient. In order to improve their business, it is necessary, above all, to more efficiently manage their operating income and profits, by applying the "new business models" (i.e. cost management concepts, concepts of customer rotation, concept of sustainable development). This also applies to more efficient management of human capital. The significant role of employees in creating the added value for insurance companies in the Republic of Serbia. To this purpose (in order to increase efficiency), significant attention should be paid to life insurance, which has recorded a significant growth, year after year.
Keywords: C61; G22; L25; M41; 330; market share; profit per employee; strategic profit model; DEA model